All the truth that's in me - Berry, Julie, 1974- (Durking, Surrey : Templar, 2013)
"Judith can't speak. But when her close-knit community of Roswell Station is attacked by enemies, Judith is forced to choose: continue to live in silence, or recover her voice"--Publisher.
Young Adult.
Young Adult
Keywords: Community life -- Juvenile fiction; Selective mutism -- Juvenile fiction; Community life -- Fiction; Selective mutism -- Fiction; War -- Fiction; Community life -- Fiction; Selective mutism -- Fiction; War stories; War stories